Experimental study on different recycled aggregagtes towards strength of hardened concrete - Lim Suo Teck (School of Environmental Engineering, University Malaysia Perlis, 2014)
Conservation of natural resources and preservation of environment is the essence of any development. The problem arising from continuous technological and industrial development is the disposal of the waste material. If some of the waste materials are found suitable in concrete making, not only cost of construction can be cut down, but also safe disposal of waste materials can be achieved. So in the present paper, an attempt has been made to assess the suitability of stone dust and ceramic scrap in concrete making.